Law Enforcement of Transnational Cybercrime: Case Study in Indonesia - Martono, Martono; Gagarin Akbar, M. Gary; Rahmatiar, Y (Universitas Muhammadiyah Sumatera Utara, 2025)
Transnational cybercrime is a common problem in governance amidst digitalization and even across national borders, thus requiring a fast, adaptive, and international cooperation-based legal response. The purpose of this study is to analyze the Indonesian national legal system in responding to transnational cybercrime, including identifying emerging obstacles and institutional responses and multinational cooperation that have been formed. The approach used is normative juridical, by analyzing primary and secondary legal materials that refer to the case and perception approaches to legal regulations. The results of this study are that Indonesia already has a number of legal instruments used to prosecute cybercrime, such as the ITE Law, the Criminal Code, and international legal instruments such as the Mutual Assistance Law (MLA) and Indonesia's participation in the United Nations Convention Against Transnational Organized Crime (UNTOC). On the institutional side, the existence of the Cyber Crime Directorate, BSSN, and other related agencies is an important foundation in detection and enforcement efforts, but there are still obstacles such as limited jurisdiction, lack of harmonization of international regulations, and limited technology and human resources. One of the case studies analyzed revealed the complexity in the law enforcement process for cybercrime involving perpetrators from abroad and causing major financial losses in Indonesia.